The Effect of Macroeconomic Variables and The Stock Market on The Financial Performance of Companies Two Years After The Merger and Acquisition - Novita Emildasari; Dewi Tamara (Ridwan Institute, 2021)
This research is to identify the company's financial performance after two years of merging and acquisition. This research analyzes the effect of Money Supply, Inflation and Foreign Exchange) and the stock trading volume, earning per share, and price to earning ratio) on yield and capital gain. The population is companies that did mergers & acquisitions in 2018. This research data is monthly data throughout 2018 and 2020. Data analysis techniques include regression of panel data using views 10, and Chow, Lagrange Multiplier, and Hausman test). The results are there is an increase in the stock market performance and variables of capital gain, yield, trade volume activity earnings per share, except for price to earning ratio. Foreign exchange, trading volume, EPS, and PER have a positive and significant impact on capital gains and yields. Meanwhile, money supply and inflation insignificantly positive affect capital gains and yields